Clinical Features and Outcomes of Treatment for Fourth Nerve Palsy - Bagheri, Abbas (Ophthalmic Research Center, 2010)
PURPOSE: To evaluate the clinical features, etiology and outcomes of treatment for superior oblique (SO) palsy over a 10-year period at Labbafinejad Medical Center. METHODS: A complete ophthalmologic examination with particular attention to forced duction test (FDT) and tendon laxity was performed in all patients preoperatively. The palsy was divided into congenital and acquired types. RESULTS: Overall, 73 patients including 45 male (61.6%) and 28 female (38.4%) subjects with mean age of 19.7±11.7 (range, 1.5–62) years, were operated from 1997 to 2007. SO palsy was congenital in 56 (76%) and acquired in 17 (24%) cases. The most common chief complaint was ocular deviation (52.1%). FDT was positive in only 7 (9.7%) cases. Other clinical findings included amblyopia (19.2%), head tilt (13.7%), chin down position (4.1%), facial asymmetry (6.8%) and tendon laxity (2.7%). Mean preoperative vertical deviation was 16.1 prism diopters (PD) which was decreased to 1.9 PD postoperatively. Mean exotropia and esotropia were 15 and 13.9 PD respectively before the operation and both decreased to 1.5 PD of horizontal deviation postoperatively. The most common type of SO palsy based on Knapp’s classification was type 3 (42.5%). The most common operated muscle was the inferior oblique (83.6%) and the most common type of operation was inferior oblique myectomy (83.6%). The success rate for initial surgery was 84% and was increased to 96% with a second intervention. CONCLUSION: The most common form of SO palsy requiring surgical intervention was congenital which occurred most frequently in young males. Most cases of SO palsy can be successfully treated with a single surgical procedure.